2012
DOI: 10.7744/cnujas.2012.39.2.243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural antioxidant extracted from Citrus junos seib. or Prunus mume. on the quality traits of sun-dried Hanwoo beef jerky

Abstract: :The objective of the study was to evaluate the quality characteristics of sun-dried Hanwoo beef jerky added with the extract of Citrus junos seib. or Prunus mume. Hanwoo beef shank muscles were sliced, marinated, and sun-dried at 25°C, relative humidity of 35%. The physicochemical quality and microbiological safety of the Hanwoo beef jerky aerobically packaged were analyzed during the storage of 25°C. The moisture content of beef jerky with Citrus junos seib. was the lowest among the treatments after 20 d. Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“… Kim et al (2013b) had reported similar results of increased total aerobic bacterial count, in addition to no detected mold and coliform bacterial populations in pork jerky during a 2 month storage period, regardless of the control (without leek extract); the jerky was prepared with leek extract. Lim et al (2012) had also reported that the total plate count of sun-dried beef jerky increased regardless of the addition of Citrus junos seib and Prunus mume extracts during storage. Several studies have noted that the fermented loquat leaf ethanol extract possesses antimicrobial activity and that the differences in the quantity of loquat LE can result in differences in their antimicrobial activity, which can consequently affect microbial growth on meat products with loquat LE ( Dhiman et al, 2021 ; Fu et al, 2019 ; Liu et al, 2016 ).…”
Section: Resultsmentioning
confidence: 98%
“… Kim et al (2013b) had reported similar results of increased total aerobic bacterial count, in addition to no detected mold and coliform bacterial populations in pork jerky during a 2 month storage period, regardless of the control (without leek extract); the jerky was prepared with leek extract. Lim et al (2012) had also reported that the total plate count of sun-dried beef jerky increased regardless of the addition of Citrus junos seib and Prunus mume extracts during storage. Several studies have noted that the fermented loquat leaf ethanol extract possesses antimicrobial activity and that the differences in the quantity of loquat LE can result in differences in their antimicrobial activity, which can consequently affect microbial growth on meat products with loquat LE ( Dhiman et al, 2021 ; Fu et al, 2019 ; Liu et al, 2016 ).…”
Section: Resultsmentioning
confidence: 98%